The diagnostic pathway of oropharyngeal squamous cell carcinoma in a large U.S. healthcare system. (15th December 2017) - Gilde, Jason; Song, Brian; Masroor, Farzad; Darbinian, Jeanne A.; Ritterman Weintraub, Miranda L.; Salazar, James; Yang, Eleanor; Gurushanthaiah, Deepak; Wang, Kevin H.
Abstract : Objective: To examine the current diagnostic pathway of oropharyngeal squamous cell carcinoma (OPSCC) and identify factors associated with time to diagnosis. Methods: Retrospective cohort study of patients with OPSCC in an integrated healthcare system from January 1, 2013, to December 31, 2013. Patient demographics, tobacco and alcohol use, chief complaint, tumor stage, human papilloma virus (HPV) status, physician factors (diagnosis, antibiotic prescription, performance of endoscopic exam, biopsy), and time intervals were examined. Time variations by patient characteristics and physician practice were assessed. Results: We identified 152 patients with OPSCC. Of those, 90% had stage III to IV disease. The cohort was largely male (85%), white (79%), with HPV‐positive tumors (84%). Most common chief complaints were neck mass (52%) and sore throat (20%). Among those with neck a mass, 94% had HPV‐positive tumors. Prescription of antibiotics was associated with longer time to first otolaryngology evaluation. Median time from symptom onset to first primary care physician (PCP) contact was 3.0 weeks; from PCP to otolaryngologist was 1.1 weeks, and from otolaryngologist to tissue diagnosis was 0.4 weeks. At the first otolaryngology visit, 82% underwent in‐office flexible endoscopy and 58% had same‐day biopsy, resulting in rapid time to tissue diagnosis. Diagnostic time intervals did not differ by HPV status. Conclusion: The overall diagnostic process was efficient, although initial antibiotic treatment resulted in longer time to first otolaryngology visit. Tumor HPV status was associated with presenting findings but not time to diagnosis. The variation in diagnostic delay time and impact on survival outcomes is unknown and merits further investigation. Level of Evidence: 4. Laryngoscope, 1867–1873, 2018